Antidepressant-Like Effect of Sodium Butyrate is Associated with an Increase in TET1 and in 5-Hydroxymethylation Levels in the Bdnf Gene - Wei, Ya Bin; Melas, Philippe A.; Wegener, Gregers; Mathé, Aleksander A.; Lavebratt, Catharina (The international journal of neuropsychopharmacology, 2015)
Background:Epigenetic drugs like sodium butyrate (NaB) show antidepressant-like effects in preclinical studies, but the exact molecular mechanisms of the antidepressant effects remain unknown. While research using NaB has mainly focused on its role as a histone deacetylase inhibitor (HDACi), there is also evidence that NaB affects DNA methylation.Methods:The purpose of this study was to examine NaB’s putative antidepressant-like efficacy in relation to DNA methylation changes in the prefrontal cortex of an established genetic rat model of depression (the Flinders Sensitive Line [FSL]) and its controls (the Flinders Resistant Line).Results:The FSL rats had lower levels of ten-eleven translocation methylcytosine dioxygenase 1 (TET1), which catalyzes the conversion of DNA methylation to hydroxymethylation. As indicated by the behavioral despair test, chronic administration of NaB had antidepressant-like effects in the FSL and was accompanied by increased levels of TET1. The TET1 upregulation was also associated with an increase of hydroxymethylation and a decrease of methylation in brain-derived neurotrophic factor (Bdnf), a gene associated with neurogenesis and synaptic plasticity. These epigenetic changes were associated with a corresponding BDNF overexpression.Conclusions:Our data support the antidepressant efficacy of HDACis and suggest that their epigenetic effects may also include DNA methylation changes that are mediated by demethylation-facilitating enzymes like TET1.